Janus-faced spatacsin (SPG11): involvement in neurodevelopment and multisystem neurodegeneration - Pozner, Tatyana; Regensburger, Martin; Engelhorn, Tobias; Winkler, Jürgen; Winner, Beate (Brain, 2020)
Hereditary spastic paraplegia (HSP) is a heterogeneous group of rare motor neuron disorders characterized by progressive weakness and spasticity of the lower limbs. HSP type 11 (SPG11-HSP) is linked to pathogenic variants in the SPG11 gene and it represents the most frequent form of complex autosomal recessive HSP. The majority of SPG11-HSP patients exhibit additional neurological symptoms such as cognitive decline, thin corpus callosum, and peripheral neuropathy. Yet, the mechanisms of SPG11-linked spectrum diseases are largely unknown. Recent findings indicate that spatacsin, the 280 kDa protein encoded by SPG11, may impact the autophagy-lysosomal machinery. In this update, we summarize the current knowledge of SPG11-HSP. In addition to clinical symptoms and differential diagnosis, our work aims to link the different clinical manifestations with the respective structural abnormalities and cellular in vitro phenotypes. Moreover, we describe the impact of localization and function of spatacsin in different neuronal systems. Ultimately, we propose a model in which spatacsin bridges between neurodevelopmental and neurodegenerative phenotypes of SPG11-linked disorders.
CRIS-Team Scopus Importer:2020-09-04
Keywords: autophagy; hereditary spastic paraplegia; neurodegeneration; neurodevelopment; SPG11